Legal Protection Of Consumers Due To The Price Of Display Shelves (Case Study Of Indomaret West Halmahera in 2022) - Wahyu Danang Setiadi; Yuniar Rahmatiar; Muhamad Abas (Warmadewa Press, 2024)
Consumers are often confronted with business practices that tend to disadvantage them. One such practice is when the price displayed on a product's display box differs from the price at the store cashier. Given the uncertainty about the price of an item, this can negatively impact buyers. Regulations aimed at protecting consumers and providing legal clarity must exist. One such law, Consumer Protection Regulation Number 8 of 1999, describes how consumer rights are protected by the law and how this law is implemented in day-to-day social interactions. With a qualitative approach, the research methodology normative juridical approach. The findings of this journal highlight that permissible cover to consumers who endure losses because of price discrepancies involves various individuals or business entities, whether legal or not, established and operating subject to the legal domain of the Republic of Indonesia, either individually or collectively through business agreements in different market sectors. Additionally, the research notes that sanctions for businesses occur when consumers request a recalculation based on display prices, and Indomaret employees refuse. Consumers who feel aggrieved and wish to cancel their purchase and receive a refund are also denied, as transactions have been input into the cashier system. Such actions are inconsistent with regulations and disadvantage consumers.